European policies for (vocational) education and training in the Greek context - Vasilopoulos, Andreas (Adult Education Critical Issues, 2024)
The present paper seeks to explore the contemporary role and the objectives served by the transfer of European LLL policies for (vocational) education and training in Greece. Ultimately, what emerges is that, in the Greek context, we do not know the imprint of European LLL policies on the economy and employment, while, correspondingly, it appears that social inequalities in terms of access to and participation in (vocational) education and training have been exacerbated and, in the end, the relationship between social and education policies is being reshaped.